2016
DOI: 10.1111/bph.13516
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgolide K protects the heart against endoplasmic reticulum stress injury by activating the inositol‐requiring enzyme 1α/X box‐binding protein‐1 pathway

Abstract: *These two authors contributed equally to this work. BACKGROUND AND PURPOSEEndoplasmic reticulum (ER) stress is increasingly recognized as an important causal factor of many diseases. Targeting ER stress has now emerged as a new therapeutic strategy for treating cardiovascular diseases. Here, we investigated the effects and underlying mechanism of ginkgolide K (1,10-dihydroxy-3,14-didehydroginkgolide, GK) on cardiac ER stress. EXPERIMENTAL APPROACHCell death, apoptosis and ER stress-related signalling pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 61 publications
1
40
0
Order By: Relevance
“…However, in patients with previous history of hypertension and heart disease, sunitinib appears to increase the risk for cardiovascular disease (Chu et al, ). Recently, Ginkgolide K (1,10‐dihydroxy‐3,14‐didehydroginkgolide, GK), a diterpene lactone isolated from the leaves of Ginkgo biloba , has been demonstrated to protect cardiomyocytes from ER stress‐induced apoptosis both in vitro and in vivo (Wang et al, ). In response to ER stress, GK can selectively activate the IRE1α/XBP1 pathway and inhibit the activation of RIDD and JNK (Wang et al, ).…”
Section: Upr As a Therapeutic Target In Cardiac Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in patients with previous history of hypertension and heart disease, sunitinib appears to increase the risk for cardiovascular disease (Chu et al, ). Recently, Ginkgolide K (1,10‐dihydroxy‐3,14‐didehydroginkgolide, GK), a diterpene lactone isolated from the leaves of Ginkgo biloba , has been demonstrated to protect cardiomyocytes from ER stress‐induced apoptosis both in vitro and in vivo (Wang et al, ). In response to ER stress, GK can selectively activate the IRE1α/XBP1 pathway and inhibit the activation of RIDD and JNK (Wang et al, ).…”
Section: Upr As a Therapeutic Target In Cardiac Diseasesmentioning
confidence: 99%
“…Recently, Ginkgolide K (1,10‐dihydroxy‐3,14‐didehydroginkgolide, GK), a diterpene lactone isolated from the leaves of Ginkgo biloba , has been demonstrated to protect cardiomyocytes from ER stress‐induced apoptosis both in vitro and in vivo (Wang et al, ). In response to ER stress, GK can selectively activate the IRE1α/XBP1 pathway and inhibit the activation of RIDD and JNK (Wang et al, ). Therefore, GK has a potential for treating cardiovascular diseases.…”
Section: Upr As a Therapeutic Target In Cardiac Diseasesmentioning
confidence: 99%
“…GK has been reported to exhibit protective effects against glutamate cytotoxicity and H 2 O 2 -induced cytotoxicity in PC12 cells ( 21 , 22 ). GK also protects the heart against endoplasmic reticulum stress by activating the inositol-requiring enzyme 1a/X box-binding protein-1 pathway ( 23 ), and against acute ischemic stroke caused by MCAO through antioxidative effects ( 24 ). To the best of our knowledge, there has been no comparative study of GB and GK or a study examining the role of GK on astrocytes exposed to oxygen-glucose deprivation (OGD).…”
Section: Introductionmentioning
confidence: 99%
“…Ginkgolide K (GK) is an extract isolated from the leaves of Ginkgo biloba, which is another traditional herb widely used for cardiovascular diseases. A study reported by Wang et al (2016c) indicated that GK enhanced autophagic flux by increasing the expression of Beclin-1 and LCB in Tunicamycin treated neonatal rat cardiomyocytes, and demonstrated cardioprotective effects. However, the exact mechanism by which GK boosts the autophagic response remains unclear.…”
Section: Rhizoma Coptidismentioning
confidence: 97%